High-strength flame-retardant polypropylene composite material and preparation method thereof

By adding active fillers and homemade halogen-free high-efficiency flame retardant to polypropylene, high-strength flame retardant polypropylene composite materials are prepared, which solves the problem of poor flame retardant polypropylene, and improves strength, toughness and aging resistance, while ensuring flame retardant.

CN119552450AActive Publication Date: 2025-03-04SOUTH CHINA UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411701080.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Polypropylene has poor flame retardancy, is prone to combustion and produces violent chemical reactions, leading to the production of heat and melt droplets, which may cause fire or explosion, limiting its application prospects.

Method used

The composite material of 65-85 parts of polypropylene resin, 12-24 parts of active filler, 8-15 parts of halogen-free high-efficiency flame retardant, 6-12 parts of toughening agent, 2-4 parts of lubricant, 0.6-1.2 parts of antioxidant and 0.5-1 part of light stabilizer was prepared by the melt extrusion granulation process of a twin-screw extrusion machine.

Benefits of technology

It realizes the high-strength flame retardancy of polypropylene composite materials, improves its strength and aging resistance, and ensures flame retardancy. It is suitable for many areas with high performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552450A_ABST
    Figure CN119552450A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength flame-retardant polypropylene composite material and a preparation method thereof.The polypropylene composite material is prepared from, by weight, 65-85 parts of polypropylene resin, 12-24 parts of active filler, 8-15 parts of halogen-free efficient flame retardant, 6-12 parts of flexibilizer, 2-4 parts of lubricant, 0.6-1.2 parts of antioxidant and 0.5-1 part of light stabilizer; the polypropylene composite material prepared by the preparation method disclosed by the invention not only has relatively high flame retardance, but also is relatively well improved in strength and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of plastic products, and in particular to a high-strength flame-retardant polypropylene composite material and a preparation method thereof. Background Art

[0002] Polypropylene, referred to as PP, is a colorless, odorless, non-toxic, translucent solid substance. Polypropylene is a thermoplastic synthetic resin with excellent performance. It is a colorless, translucent thermoplastic lightweight general-purpose plastic with chemical resistance, heat resistance, electrical insulation, high-strength mechanical properties and good high-wear processing performance. Since its advent, polypropylene has been rapidly developed and applied in many fields such as machinery, automobiles, electronic appliances, construction, textiles, packaging, agriculture, forestry, fishery and food industry. Because polypropylene has good plasticity, it is gradually replacing wooden products, and its high strength, toughness and high wear resistance have gradually replaced the mechanical functions of metals. In addition, polypropylene has good grafting and composite functions, and has huge application space in concrete, textiles, packaging and agriculture, forestry and fishery.

[0003] However, polypropylene has poor flame retardancy. Its molecules contain unstable carbon-hydrogen bonds, and its limiting oxygen index is less than 20%. It is very easy to burn, and the combustion of polypropylene is a very violent and complex chemical reaction process. In the combustion process, not only a large amount of heat is generated, but also a large amount of molten droplets are generated. The molten droplets can ignite other combustibles, and then spread the flame. In severe cases, it can even cause an explosion, which has brought serious obstacles to the application prospects of polypropylene. Most of the flame retardants on the market are not suitable for polypropylene. Not only does the flame retardant effect not improve significantly, but it is also easy to cause its strength to decrease. Summary of the invention

[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a high-strength flame-retardant polypropylene composite material and a preparation method thereof.

[0005] The purpose of the present invention is achieved by adopting the following technical solutions:

[0006] In a first aspect, the present invention provides a high-strength flame-retardant polypropylene composite material, calculated by weight, comprising:

[0007] 65-85 parts of polypropylene resin, 12-24 parts of active filler, 8-15 parts of halogen-free high-efficiency flame retardant, 6-12 parts of toughening agent, 2-4 parts of lubricant, 0.6-1.2 parts of antioxidant and 0.5-1 parts of light stabilizer.

[0008] Preferably, the polypropylene resin is 0.89-0.91 g / cm 3 , the melt flow rate is 2.8-3.6 g / 10 min (230°C, 2.16 kg).

[0009] Preferably, the active filler is nano-active calcium carbonate, which is prepared by treating nano-scale ultrafine calcium carbonate with a titanate coupling agent.

[0010] Preferably, the halogen-free high-efficiency flame retardant is prepared by aldehyde-amine condensation of aminated phosphoramide and aldehyde-substituted benzoxazine.

[0011] Preferably, the toughening agent is polyolefin elastomer POE, and the brand is one or a combination of Dow POE-8540, Dow POE-8150, and Dow POE-8150.

[0012] Preferably, the lubricant is a mixture of vinyl bisstearamide and magnesium stearate, and the mass ratio of vinyl bisstearamide to magnesium stearate is 2-5:1.

[0013] Preferably, the antioxidant is one or a combination of antioxidant 1024, antioxidant 1010, antioxidant 168, antioxidant 626, and antioxidant 702.

[0014] Preferably, the light stabilizer is one or a combination of light stabilizer UV-770, light stabilizer UV-944, light stabilizer UV-234, light stabilizer UV-329, and light stabilizer UV-1577.

[0015] Preferably, the preparation process of the active filler comprises:

[0016] Add titanate coupling agent into toluene, fully dissolve it, add nano-scale ultrafine calcium carbonate powder, first disperse it evenly by ultrasonication, then stir it at a temperature of 50-70°C and a speed of 800-1000r / min for 10-20min, then remove the solvent under reduced pressure to obtain active filler;

[0017] The particle size of the nano-scale calcium carbonate powder is 80-100 nm, and the model of the titanate coupling agent is GR-201 or GR-401;

[0018] Wherein, the mass ratio of nano-scale ultrafine calcium carbonate powder, titanate coupling agent and toluene is 1:0.02-0.08:10-20.

[0019] Preferably, the preparation method of the halogen-free high-efficiency flame retardant comprises:

[0020] S1, preparation of phosphoramide amination:

[0021] The urea and triethyl phosphate are heated to 105-125°C under the protection of nitrogen, and stirred for 8-12 hours. After the reaction, the reaction product is dissolved in anhydrous ethanol, and then purified and dried to obtain amino phosphoramide;

[0022] Wherein, the mass ratio of urea to triethyl phosphate is 1.8-2.4:0.7-1.4;

[0023] The purification is performed by chromatography on a silica gel column, and the eluent is ethyl acetate and dichloromethane in a volume ratio of 1:6-10.

[0024] S2. Preparation of aldehyde-substituted benzoxazine:

[0025] In an ice-water bath, 1-aminobutane is mixed into a formaldehyde aqueous solution, stirred for 1-3 hours, then heated to 65-75°C, stirred for half an hour, then p-hydroxybenzaldehyde is slowly added, and stirred for 6-12 hours. After the reaction is completed, the aldehyde-modified benzoxazine is obtained after washing and drying;

[0026] The mass fraction of the aqueous solution of formaldehyde is 35%-40%, and the mass ratio of 1-aminobutane, p-hydroxybenzaldehyde and the aqueous solution of formaldehyde is 0.73-1.46:1.2-2.4:15-25;

[0027] The washing process includes washing with alkaline solution, washing with acid solution and washing with pure water in sequence, wherein the alkaline solution is 0.1 mol / L sodium hydroxide solution, and the acid solution is 0.1 mol / L hydrochloric acid solution; washing with alkaline solution three times, washing with acid solution three times, and then washing with pure water until the washing solution is neutral;

[0028] Wherein, drying is carried out under vacuum conditions at 50-80°C;

[0029] S3. Preparation of flame retardant precursor:

[0030] The amino phosphoramide and the aldehyde benzoxazine are mixed in dimethyl sulfoxide, stirred until uniformly dissolved, and then heated to 90-120° C., stirred and reacted for 4-10 hours under the action of a catalyst, and after the reaction is completed, the solvent is removed by rotary evaporation to obtain a flame retardant precursor;

[0031] Wherein, the mass ratio of the amidated phosphoramide, the aldehyded benzoxazine and the dimethyl sulfoxide is 1.3-2.6:1.1-2.2:30-50.

[0032] The catalyst is glacial acetic acid, and the added amount is 1.5%-7.5% of the mass of the amide phosphoramide;

[0033] S4, post-processing:

[0034] The flame retardant precursor is subjected to a heating treatment at 120-250° C. to obtain a halogen-free high-efficiency flame retardant.

[0035] Preferably, the temperature-raising treatment is a staged temperature-raising treatment, that is, the temperature is successively 120° C., 150° C., 200° C. and 250° C. for 2-4 hours.

[0036] In a second aspect, the present invention provides a method for preparing a high-strength flame-retardant polypropylene composite material, comprising the following steps:

[0037] (1) Weighing polypropylene resin, active filler, halogen-free high-efficiency flame retardant, toughening agent, lubricant, antioxidant and light stabilizer, mixing them in a blender, and rapidly stirring and mixing to obtain a mixed raw material;

[0038] (2) The mixed raw materials are fed into a twin-screw extruder, and melt-extruded and granulated in a temperature range of 195-225° C. to finally obtain a polypropylene composite material.

[0039] Preferably, the stirring speed in the stirrer is 400-600 r / min, and the stirring time is 2-10 min.

[0040] Preferably, the temperature ranges of the twin-screw extruder include: zone 1 195-205°C, zone 2 210-220°C, zone 3 215-225°C, zone 4 220-225°C, zone 5 220-225°C, zone 6 215-220°C, zone 7 210-220°C, the screw aspect ratio is 32-40:1, and the rotation speed is 100-150r / min.

[0041] The beneficial effects of the present invention are:

[0042] 1. The present invention prepares a polypropylene composite material, which uses polypropylene resin as the main material and nano-activated calcium carbonate as the filler. It also uses a homemade halogen-free high-efficiency flame retardant, as well as additives such as a toughening agent, a lubricant, an antioxidant and a light stabilizer. The prepared polypropylene composite material not only has strong flame retardancy, but also has improved strength and aging resistance.

[0043] 2. The halogen-free high-efficiency flame retardant of the present invention is prepared by aldehyde-amine condensation of aminated phosphoramide and aldehyde-substituted benzoxazine. Among them, the aminated phosphoramide is prepared with urea and triethyl phosphate as raw materials, and the aldehyde-substituted benzoxazine is prepared with 1-aminobutane (n-butylamine), formaldehyde and p-hydroxybenzaldehyde as raw materials. The halogen-free high-efficiency flame retardant prepared by the present invention contains structures such as benzoxazine, phosphoramide and Schiff base, so that the flame retardancy is guaranteed while improving the strength and aging resistance of polypropylene materials.

[0044] 3. The active filler used in the present invention is prepared by treating nano-scale ultrafine calcium carbonate with a titanate coupling agent. The treatment process is carried out in a solvent. After heating and high-speed stirring, the solvent is removed to obtain the desired active filler. The surface activity of the treated filler is enhanced, so that the adhesion with the resin is better, and the titanate coupling agent coated on the surface can also improve the performance of the polypropylene material. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0046] Figure 1 It is a scanning electron microscope (SEM) schematic diagram of the halogen-free high-efficiency flame retardant prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0048] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0049] The present invention will be further described below in conjunction with the following examples.

[0050] Example 1

[0051] A high-strength flame-retardant polypropylene composite material, calculated by weight, comprising:

[0052] 75 parts of polypropylene resin, 18 parts of active filler, 12 parts of halogen-free high-efficiency flame retardant, 9 parts of toughening agent, 3 parts of lubricant, 0.8 parts of antioxidant and 0.6 parts of light stabilizer.

[0053] Among them, polypropylene resin is 0.90g / cm 3 , the melt flow rate is 3.2g / 10min (230℃, 2.16kg); the toughening agent is polyolefin elastomer POE, brand Dow POE-8540; the lubricant is vinyl bisstearamide and magnesium stearate mixed in a mass ratio of 3:1; the antioxidant is antioxidant 1024; the light stabilizer is light stabilizer UV-770.

[0054] The preparation process of the active filler includes:

[0055] The titanate coupling agent GR-201 is added to toluene and fully dissolved, and then ultrafine calcium carbonate powder with a particle size of 80-100nm is added. The mass ratio of nano-scale ultrafine calcium carbonate powder, titanate coupling agent and toluene is 1:0.05:15. Ultrasonic dispersion is first performed uniformly, and then stirring is performed at a temperature of 60°C and a speed of 900r / min for 15min. After that, the solvent is removed under reduced pressure to obtain an active filler.

[0056] The preparation method of the halogen-free high-efficiency flame retardant comprises:

[0057] S1, urea and triethyl phosphate were mixed in a reaction flask, the mass ratio of urea to triethyl phosphate was 2.1:1.1, after fully stirring, nitrogen was introduced as a protective gas, the temperature was raised to 115 ° C, and the reaction was stirred for 10 hours. After the reaction was completed, the reaction product was dissolved in 5 volumes of anhydrous ethanol, and then chromatographed on a silica gel column, with ethyl acetate and dichloromethane in a volume ratio of 1:8 as an eluent, and after elution, the amide was obtained after rotary evaporation and drying;

[0058] S2. In an ice-water bath, 1-aminobutane was mixed into a 37 wt% aqueous solution of formaldehyde, stirred for 2 h, then transferred to a reflux condenser, heated to 70 ° C, kept warm and stirred for half an hour, and then p-hydroxybenzaldehyde was slowly added. The mass ratio of 1-aminobutane, p-hydroxybenzaldehyde and the aqueous solution of formaldehyde was 1.11:1.8:20. The mixture was kept warm and stirred for 9 h. After the reaction was completed, it was first washed three times with a 0.1 mol / L sodium hydroxide solution, then washed three times with a 0.1 mol / L hydrochloric acid solution, and finally washed with pure water until the washing liquid was neutral. Drying was performed under vacuum conditions at 60 ° C to obtain formaldehyde benzoxazine;

[0059] S3, mixing the amidated phosphoramide and the aldehyde-substituted benzoxazine in dimethyl sulfoxide, wherein the mass ratio of the amidated phosphoramide, the aldehyde-substituted benzoxazine and the dimethyl sulfoxide is 2.1:1.7:40, stirring until uniformly dissolved, heating to 110° C., adding 4.5% glacial acetic acid of the mass of the amidated phosphoramide as a catalyst, keeping the temperature and stirring for 8 hours, and after the reaction is completed, removing the solvent by rotary evaporation to obtain a precursor;

[0060] S4. Treat the precursor at 120°C, 150°C, 200°C and 250°C for 3 hours in sequence. After the treatment, cool it to room temperature to obtain the desired halogen-free high-efficiency flame retardant.

[0061] The method for preparing the high-strength flame-retardant polypropylene composite material comprises the following steps:

[0062] (1) Weighing polypropylene resin, active filler, halogen-free high-efficiency flame retardant, toughening agent, lubricant, antioxidant and light stabilizer, mixing them in a blender, and stirring at a speed of 500 r / min for 7 min to obtain a mixed raw material;

[0063] (2) The mixed raw materials are put into a twin-screw extruder, the temperature range of the twin-screw extruder includes: zone 1 200°C, zone 2 215°C, zone 3 215°C, zone 4 220°C, zone 5 225°C, zone 6 220°C, zone 7 210°C, the screw aspect ratio is 36:1, the rotation speed is 120r / min, and the desired polypropylene composite material is obtained through melt extrusion granulation.

[0064] Example 2

[0065] A high-strength flame-retardant polypropylene composite material, calculated by weight, comprising:

[0066] 65 parts of polypropylene resin, 12 parts of active filler, 8 parts of halogen-free high-efficiency flame retardant, 6 parts of toughening agent, 2 parts of lubricant, 0.6 parts of antioxidant and 0.5 parts of light stabilizer.

[0067] Among them, polypropylene resin is 0.90g / cm 3 , the melt flow rate is 3.2g / 10min (230℃, 2.16kg). The toughening agent is polyolefin elastomer POE, brand is American Dow POE-8150; the lubricant is a mixture of vinyl bis stearamide and magnesium stearate, the mass ratio of vinyl bis stearamide and magnesium stearate is 2:1; the antioxidant is antioxidant 1010; the light stabilizer is light stabilizer UV-944.

[0068] The preparation process of the active filler includes:

[0069] The titanate coupling agent GR-201 is added to toluene and fully dissolved, and then ultrafine calcium carbonate powder with a particle size of 80-100 nm is added, firstly ultrasonically dispersed evenly, and then stirred at a temperature of 50°C and a speed of 800 r / min for 10 minutes, and then the solvent is removed under reduced pressure to obtain an active filler; the mass ratio of nano-scale ultrafine calcium carbonate powder, titanate coupling agent and toluene is 1:0.02:10.

[0070] The preparation method of the halogen-free high-efficiency flame retardant comprises:

[0071] S1. Mix urea and triethyl phosphate in a reaction flask, the mass ratio of urea to triethyl phosphate is 1.8:0.7, stir well, introduce nitrogen as protective gas, heat to 105°C, keep warm and stir for 8h, after the reaction, dissolve the reaction product in 4 times the volume of anhydrous ethanol, and then chromatograph on a silica gel column, the eluent is: ethyl acetate and dichloromethane in a volume ratio of 1:6, and rotary evaporate to obtain amino phosphoramide;

[0072] S2. In an ice-water bath, 1-aminobutane was mixed into a 37 wt% aqueous solution of formaldehyde, stirred for 1 h, then transferred to a reflux condenser, heated to 65 ° C, stirred for half an hour, and then p-hydroxybenzaldehyde was slowly added. The mass ratio of 1-aminobutane, p-hydroxybenzaldehyde and the aqueous solution of formaldehyde was 0.73:1.2:15. The mixture was stirred for 6 h. After the reaction was completed, it was washed three times with a 0.1 mol / L sodium hydroxide solution, and then washed three times with a 0.1 mol / L hydrochloric acid solution. Finally, it was washed with pure water until the washing liquid was neutral, and dried under vacuum at 50 ° C to obtain the formaldehyde benzoxazine;

[0073] S3, mixing the amidated phosphoramide and the aldehyde-substituted benzoxazine in dimethyl sulfoxide, the mass ratio of the amidated phosphoramide, the aldehyde-substituted benzoxazine and the dimethyl sulfoxide being 1.3:1.1:30, stirring until uniformly dissolved, heating to 90° C., adding 1.5% glacial acetic acid of the mass of the amidated phosphoramide as a catalyst, keeping the temperature and stirring for 4 hours, and after the reaction is completed, removing the solvent by rotary evaporation to obtain a precursor;

[0074] S4. Treat the precursor at 120°C, 150°C, 200°C and 250°C for 2h in sequence, and cool to room temperature after the treatment to obtain the desired halogen-free high-efficiency flame retardant.

[0075] The method for preparing the high-strength flame-retardant polypropylene composite material comprises the following steps:

[0076] (1) Weighing polypropylene resin, active filler, halogen-free high-efficiency flame retardant, toughening agent, lubricant, antioxidant and light stabilizer, mixing them in a blender, and stirring at a speed of 400 r / min for 2 min to obtain a mixed raw material;

[0077] (2) The mixed raw materials are put into a twin-screw extruder, the temperature range of the twin-screw extruder includes: zone 1 195°C, zone 2 210°C, zone 3 215°C, zone 4 220°C, zone 5 220°C, zone 6 215°C, zone 7 210°C, the screw aspect ratio is 32:1, the rotation speed is 100r / min, and the desired polypropylene composite material is obtained through melt extrusion granulation.

[0078] Example 3

[0079] A high-strength flame-retardant polypropylene composite material, calculated by weight, comprising:

[0080] 85 parts of polypropylene resin, 24 parts of active filler, 15 parts of halogen-free high-efficiency flame retardant, 12 parts of toughening agent, 4 parts of lubricant, 1.2 parts of antioxidant and 1 part of light stabilizer.

[0081] Among them, polypropylene resin is 0.90g / cm 3 , the melt flow rate is 3.2g / 10min (230℃, 2.16kg); the toughening agent is polyolefin elastomer POE, and the brand is Dow POE-8150; the lubricant is a mixture of vinyl bisstearamide and magnesium stearate, and the mass ratio of vinyl bisstearamide and magnesium stearate is 5:1; the antioxidant is antioxidant 168; the light stabilizer is light stabilizer UV-234.

[0082] The preparation process of the active filler includes:

[0083] The titanate coupling agent GR-401 is added to toluene and fully dissolved, and then ultrafine calcium carbonate powder with a particle size of 80-100 nm is added, firstly ultrasonically dispersed evenly, and then stirred at a temperature of 70°C and a speed of 1000 r / min for 20 minutes, and then the solvent is removed under reduced pressure to obtain an active filler; the mass ratio of nano-scale ultrafine calcium carbonate powder, titanate coupling agent and toluene is 1:0.08:20.

[0084] The preparation method of the halogen-free high-efficiency flame retardant comprises:

[0085] S1. Mix urea and triethyl phosphate in a reaction flask, the mass ratio of urea to triethyl phosphate is 2.4:1.4, after fully stirring, introduce nitrogen as protective gas, heat to 125°C, keep warm and stir for 12h, after the reaction, dissolve the reaction product in 6 volumes of anhydrous ethanol, and then chromatograph on a silica gel column, the eluent is: ethyl acetate and dichloromethane in a volume ratio of 1:10, and rotary evaporate to obtain aminated phosphoramide;

[0086] S2. In an ice-water bath, 1-aminobutane was mixed into a 37 wt% aqueous solution of formaldehyde, stirred for 3 h, then transferred to a reflux condenser, heated to 75 ° C, and stirred for half an hour, and then p-hydroxybenzaldehyde was slowly added. The mass ratio of 1-aminobutane, p-hydroxybenzaldehyde and the aqueous solution of formaldehyde was 1.46:2.4:25. The mixture was stirred for 12 h. After the reaction was completed, it was washed three times with a 0.1 mol / L sodium hydroxide solution, and then washed three times with a 0.1 mol / L hydrochloric acid solution. Finally, it was washed with pure water until the washing liquid was neutral, and dried under vacuum at 80 ° C to obtain the formaldehyde benzoxazine;

[0087] S3, mixing the amidated phosphoramide and the aldehyde-substituted benzoxazine in dimethyl sulfoxide, wherein the mass ratio of the amidated phosphoramide, the aldehyde-substituted benzoxazine and the dimethyl sulfoxide is 2.6:2.2:50, stirring until uniformly dissolved, heating to 120° C., adding 7.5% glacial acetic acid of the mass of the amidated phosphoramide as a catalyst, keeping the temperature and stirring for 10 hours, and after the reaction is completed, removing the solvent by rotary evaporation to obtain a precursor;

[0088] S4. Treat the precursor at 120°C, 150°C, 200°C and 250°C for 4 hours in sequence, and cool to room temperature after the treatment to obtain the desired halogen-free high-efficiency flame retardant.

[0089] The method for preparing the high-strength flame-retardant polypropylene composite material comprises the following steps:

[0090] (1) Weighing polypropylene resin, active filler, halogen-free high-efficiency flame retardant, toughening agent, lubricant, antioxidant and light stabilizer, mixing them in a blender, and stirring at a speed of 600 r / min for 10 min to obtain a mixed raw material;

[0091] (2) The mixed raw materials are put into a twin-screw extruder, the temperature range of the twin-screw extruder includes: zone 1 205°C, zone 2 220°C, zone 3 225°C, zone 4 225°C, zone 5 225°C, zone 6 220°C, zone 7 220°C, the screw aspect ratio is 40:1, the rotation speed is 150r / min, and the desired polypropylene composite material is obtained through melt extrusion granulation.

[0092] Comparative Example 1

[0093] A polypropylene composite material, which is different from Example 1 only in that the composition of the halogen-free high-efficiency flame retardant is different. The halogen-free high-efficiency flame retardant used in this comparative example is amino phosphoramide, and the preparation process is the same as step S1 of Example 1.

[0094] Comparative Example 2

[0095] A polypropylene composite material, which is different from Example 1 only in that the composition of the halogen-free high-efficiency flame retardant is different. The halogen-free high-efficiency flame retardant used in this comparative example is formaldehyde-substituted benzoxazine, and the preparation process is the same as step S2 of Example 1.

[0096] Comparative Example 3

[0097] A polypropylene composite material, which is different from Example 1 only in that the composition of the halogen-free high-efficiency flame retardant is different. The halogen-free high-efficiency flame retardant used in this comparative example is a reaction product of amidated phosphoramide and p-hydroxybenzaldehyde, and the mass ratio is converted based on Example 1. The preparation process includes:

[0098] The amidated phosphoramide and p-hydroxybenzaldehyde were mixed into dimethyl sulfoxide in a mass ratio of 2.1:1.3:40. After stirring until uniformly dissolved, the mixture was heated to 110°C, and 4.5% glacial acetic acid of the mass of the amidated phosphoramide was added as a catalyst. The mixture was stirred and reacted for 8 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a halogen-free high-efficiency flame retardant.

[0099] Comparative Example 4

[0100] A polypropylene composite material, which differs from Example 1 only in that the composition of the halogen-free high-efficiency flame retardant is different. The halogen-free high-efficiency flame retardant used in this comparative example is a mixture of amino phosphoramide and benzoxazine resin (Loctite BZ9120), which is subjected to staged heating treatment at 120-250° C. for 3 hours, and the mass ratio of amino phosphoramide to benzoxazine resin is 2.1:1.7.

[0101] Performance Testing

[0102] In order to prove the content of the present invention, the performance of the polypropylene composite materials prepared in Example 1 and Comparative Examples 1-4 of the present invention are tested with reference to the corresponding standards, wherein the tensile strength is referenced to the standard of GB / T 1040-2006, the impact strength is referenced to the standard of GB / T 1843-2008, the limiting oxygen index is referenced to the standard of GB / T 2406-1993, and the flame retardant grade is referenced to the vertical test method standard of GB / T2408-2008. The test results are shown in the following table:

[0103] Table 1 Performance display of different composite materials

[0104]

[0105] It can be seen from Table 1 above that the polypropylene composite material prepared in Example 1 of the present invention can not only maintain excellent flame retardant properties, but also have excellent strength, toughness and aging resistance, which can be explained that its comprehensive performance is better and is more suitable for fields with high requirements for multiple performance aspects.

[0106] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A high-strength flame-retardant polypropylene composite material, characterized in that: Calculated by weight, including: 65-85 parts of polypropylene resin, 12-24 parts of active filler, 8-15 parts of halogen-free high-efficiency flame retardant, 6-12 parts of toughening agent, 2-4 parts of lubricant, 0.6-1.2 parts of antioxidant and 0.5-1 parts of light stabilizer; Wherein, the active filler is nano-active calcium carbonate, which is prepared by treating nano-scale ultrafine calcium carbonate with a titanate coupling agent; The halogen-free high-efficiency flame retardant is prepared by aldehyde-amine condensation of aminophosphoramide and aldehyde-benzoxazine.

2. A high-strength flame-retardant polypropylene composite material according to claim 1, characterized in that: The toughening agent is polyolefin elastomer POE, and the brand is one or a combination of US Dow POE-8540, US Dow POE-8150, and US Dow POE-8150.

3. The high-strength flame-retardant polypropylene composite material according to claim 1, characterized in that: The lubricant is a mixture of vinyl bisstearamide and magnesium stearate, and the mass ratio of vinyl bisstearamide to magnesium stearate is 2-5:

1.

4. The high-strength flame-retardant polypropylene composite material according to claim 1, characterized in that: The antioxidant is one or a combination of antioxidant 1024, antioxidant 1010, antioxidant 168, antioxidant 626, and antioxidant 702.

5. The high-strength flame-retardant polypropylene composite material according to claim 1, characterized in that: The light stabilizer is one or a combination of light stabilizer UV-770, light stabilizer UV-944, light stabilizer UV-234, light stabilizer UV-329, and light stabilizer UV-1577.

6. The high-strength flame-retardant polypropylene composite material according to claim 1, characterized in that: The preparation process of the active filler comprises: The titanate coupling agent is added into toluene and fully dissolved, then the nano-scale ultrafine calcium carbonate powder is added, firstly dispersed evenly by ultrasonication, then stirred at a temperature of 50-70°C and a speed of 800-1000r / min for 10-20min, and then the solvent is removed under reduced pressure to obtain an active filler.

7. The high-strength flame-retardant polypropylene composite material according to claim 6, characterized in that: The mass ratio of nano-scale ultrafine calcium carbonate powder, titanate coupling agent and toluene is 1:0.02-0.08:10-20.

8. The high-strength flame-retardant polypropylene composite material according to claim 1, characterized in that: The preparation method of the halogen-free high-efficiency flame retardant comprises: S1. Heating urea and triethyl phosphate to 105-125° C. under the protection of nitrogen, stirring and reacting for 8-12 hours. After the reaction, dissolving the reaction product in anhydrous ethanol, and then purifying and drying to obtain amino phosphoramide; S2. In an ice-water bath, 1-aminobutane is mixed into an aqueous solution of formaldehyde, stirred for 1-3 hours, then heated to 65-75°C, stirred for half an hour, and then p-hydroxybenzaldehyde is slowly added. The stirring reaction is continued for 6-12 hours. After the reaction is completed, the aldehyde-modified benzoxazine is obtained by washing and drying; S3, mixing the amino phosphoramide and the aldehyde benzoxazine in dimethyl sulfoxide, stirring until uniformly dissolved, heating to 90-120° C., stirring and reacting for 4-10 hours under the action of a catalyst, and after the reaction is completed, removing the solvent by rotary evaporation to obtain a flame retardant precursor; S4. The flame retardant precursor is subjected to a heating treatment at 120-250° C. to obtain a halogen-free high-efficiency flame retardant.

9. The high-strength flame-retardant polypropylene composite material according to claim 8, characterized in that: In S1, the mass ratio of urea to triethyl phosphate is 1.8-2.4:0.7-1.4; in S2, the mass ratio of 1-aminobutane, p-hydroxybenzaldehyde and formaldehyde aqueous solution is 0.73-1.46:1.2-2.4:15-25; in S3, the mass ratio of amidated phosphoramide, aldehyded benzoxazine and dimethyl sulfoxide is 1.3-2.6:1.1-2.2:30-50.

10. A method for preparing the high-strength flame-retardant polypropylene composite material according to claim 1, characterized in that: The following steps are involved: (1) Weighing polypropylene resin, active filler, halogen-free high-efficiency flame retardant, toughening agent, lubricant, antioxidant and light stabilizer, mixing them in a blender, and rapidly stirring and mixing to obtain a mixed raw material; (2) The mixed raw materials are fed into a twin-screw extruder, and melt-extruded and granulated in a temperature range of 195-225° C. to finally obtain a polypropylene composite material.

Citation Information

Patent Citations

  • High-gloss flame-retardant polypropylene composite material and preparation method thereof

    CN103351525A

  • Low-temperature impact resistant, cracking resistant and flame-retardant polypropylene material, and preparation method and applications thereof

    CN109651749A

  • High-flame-retardant modified polypropylene and preparation method thereof

    CN110903552A

  • Phosphorous containing cyclic compound, method of preparing thereof and flameproof thermoplastic resin composition using the same

    KR100842205B1